The Effect of Corporate Financial Performance, Firm Size, and Firm Age on Firm Value with Climate Change Disclosure as a Moderator - Kurniawan, Egananda; Fitriasari, Rizka (Riset Akuntansi dan Keuangan Indonesia, 2025)
This study investigates the effect of corporate financial performance, firm size, and firm age on firm value with the implementation of climate change disclosures as a moderating variable, utilizing stakeholder theory. Climate change disclosure (CCD) as recommended by the Task Force on Climate-related Financial Disclosures (TCFD) serves as a moderating variable, which is a novelty in this study. The samples include 16 energy sector companies listed on the Indonesia Stock Exchange (IDX) between 2019 and 2023, selected through purposive sampling and analyzed by panel data regression and moderated regression. The analysis results exhibit that ROA has a positive effect on firm value, ROE has a negative effect on firm value, and firm size and firm age have no effect on firm value. CCD weakens the effect of ROA and strengthens the effect of ROE on firm value, but does not moderate the effect of firm size and firm age on firm value.